Pentingnya Inovasi Produk dan Desain Produk Terhadap Keputusan Pembelian Berulang Pada Brand Iphone di Indonesia - Sofi Kurnia Sari; Anggia Novanda Isrofani; Citra Pratiwi; Reminta Lumban Batu (University of Merdeka Malang, 2021)
This research aims to explain the effect of the product innovation variables and product design partially on the repeated purchase decisions of an iPhone smartphone. This study uses 3 variables; namely product innovation (X1), product design (X2), and repeat purchase decisions (Y). Data collection was obtained by distributing questionnaires to the iPhone user community in Indonesia. The sample used in this study amounted to 100 respondents. Analysis of the data used is descriptive analysis, verification, normality test, and regression analysis. The sampling technique of this study was Stratified Random Sampling using the Slovin formula. The type of data used in this study is primary data and secondary data. The results of this study prove that Product Innovation and Product Design have a positive and significant effect on Repeated Purchasing Decisions.